POTENSI KITOSAN DARI LIMBAH CANGKANG UDANG Penaeus monodon ASAL BINTUNI SEBAGAI BIOSORBEN LIMBAH ORGANIK DAN LOGAM BERAT PADA LIMBAH CAIR PLTD MANOKWARI - Lancyfolia Rumaropen; Bertha Mangallo; Muhammad Fajar Islam (FMIPA Universitas Papua, 2021)
The purpose of this research is to study the potency of chitosan synthesis of shrimp shells from Bintuni as a biosorbent of organic compound and heavy metal compound. The main procedure of chitosan synthesis is completed by insulating chitin from shrimp shells and then chitin is deacetilated to transform chitin to be chitosan. The wastewater were characterized to know the concentration of Total Organic Carbon (TOC), fat oil, and Zinc metal and studied the adsorption of each compound at 0,1; 0,5; 1; 2g dosage chitosan. Adsorption study result showed that chitosan can adsorb the fuel oil and Zinc metal which contained in wastewater. However, it was not adsorb the TOC compound. The yield of chitosan is 46,88%. Increasing the chitosan by up to 2 g resulted in the creasing of the adsorption effectiveness up to 99,09% for the fuel oil and 69,28% for Zinc. The maximum chitosan adsorption capacity accomplished at 0,1gram chitosan in 100 mL wastewater.